2020
DOI: 10.18632/aging.102836
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and ferroptosis by a tumor suppressing magnetic field through ROS-mediated DNA damage

Abstract: Magnetic field (MF) is being used in antitumor treatment; however, the underlying biological mechanisms remain unclear. In this study, the potency and mechanism of a previously published tumor suppressing MF exposure protocol were further investigated. This protocol, characterized as a 50 Hz electromagnetic field modulated by static MF with time-average intensity of 5.1 mT, when applied for 2 h daily for over 3 consecutive days, selectively inhibited the growth of a broad spectrum of tumor cell lines including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Excess active iron donates electrons, leading to ROS generation through the Fenton reaction, promoting lipid peroxidation and initiating ferroptosis (Dixon and Stockwell, 2014). Many researchers believe that ROS and MDA accumulation reflect the progress of cellular ferroptosis (Yamada et al, 2020;Yuan et al, 2020), while GPX4 and SOD are key antioxidant enzymes for scavenging excess ROS and MDA (Galaris et al, 2019). The role of GPX4 in ferroptosis is particularly important, studies reported that deletion of GPX4 in forebrain neurons promotes cognitive impairment and neurodegeneration (Hambright et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Excess active iron donates electrons, leading to ROS generation through the Fenton reaction, promoting lipid peroxidation and initiating ferroptosis (Dixon and Stockwell, 2014). Many researchers believe that ROS and MDA accumulation reflect the progress of cellular ferroptosis (Yamada et al, 2020;Yuan et al, 2020), while GPX4 and SOD are key antioxidant enzymes for scavenging excess ROS and MDA (Galaris et al, 2019). The role of GPX4 in ferroptosis is particularly important, studies reported that deletion of GPX4 in forebrain neurons promotes cognitive impairment and neurodegeneration (Hambright et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on cells and cell cultures showed the effectiveness of NMMA as a means of inducing apoptosis in cancer cells [ 36 , 37 , 41 , 42 ]. In addition, there is indirect evidence of the possible participation of drugs containing iron ions, or natural iron-containing proteins-ferritins, in the mechanisms of MF action in vivo [ 138 , 139 , 140 , 141 ]. Of course, for a reliable proof of the magnetomechanical origin of the effects observed in vivo, it is necessary to conduct targeted experiments with the introduction of optimally designed MNPs, with known magnetic characteristics and functional shells, into the body, as well as physically substantiated parameters of the activating AMF.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…Given that ROS is implicated in S-phase progression ( 43 , 44 ), where DNA is prone to damage ( 45–47 ), it is tempting to speculate that S70pBcl2 is the key to preventing DNA damage by reducing ROS, subsequent ROS-dependent G1/S phase transition and Ri-DNA damage. In addition, it is noted that ROS and Ri-DNA damage are upstream signals to different types of cell death such as apoptosis, necroptosis, ferroptosis or even cellular senescence ( 11 , 12 , 37 , 48–52 ). Thus, it is likely that the protective redox sensing and modulating functions of S70pBcl2 may not only be affecting the conventional apoptosis but also other types of ROS- and Ri-DNA-mediated cell deaths.…”
Section: Discussionmentioning
confidence: 99%